EFFECTIVE STRATEGIES FOR APPROPRIATE TECHNOLOGY TRAINING TO IMPROVE ENTREPRENEURSHIP IN THE DIGITAL ERA - ABDULLAH BASALAMAH; HUSAIN SYAM; MUHAMMAD YAHYA (Jurnal Vokasi Keteknikan, 2024)
This study examines effective strategies for appropriate technology training to enhance entrepreneurship in the digital era. Amid the rapid advancement of digital technology, entrepreneurship requires new approaches to leverage technologies that align with local needs and potentials. This research analyzes various training methods applied in the entrepreneurial context and identifies key factors influencing the success of such training. The findings indicate that training approaches based on local needs, user-friendly technologies, and continuous support from mentors and communities play a crucial role in developing entrepreneurial skills. Additionally, the adaptation of digital technology in training not only enhances operational efficiency but also opens new opportunities for entrepreneurs to innovate and compete in the global market. Therefore, effective training strategies can significantly impact the improvement of entrepreneurial capabilities and success in facing the challenges of the digital era. This study recommends collaboration between governments, educational institutions, and the private sector to create a holistic and sustainable training ecosystem